THE TEACHING OF ANATOMY IN NURSING EDUCATION: LEVERAGING MODERN TECHNOLOGIES FOR EFFECTIVE LEARNING (Modern education and development, 2024)
Anatomy is a foundational subject in nursing education, providing essential knowledge for understanding the human body and its functions. This paper explores the methods and strategies for teaching anatomy to nursing students, emphasizing the integration of modern technologies. With advancements in digital tools, such as virtual reality (VR), 3D models, and interactive simulations, anatomy instruction has the potential to become more engaging, accessible, and effective. This study reviews the current trends in anatomy education, discusses the benefits of technology integration, and proposes best practices for utilizing digital resources in the nursing curriculum.